2021
DOI: 10.1016/j.bbrc.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of reaction condition of recombinase polymerase amplification to detect SARS-CoV-2 DNA and RNA using a statistical method

Abstract: Recombinase polymerase amplification (RPA) is an isothermal reaction that amplifies a target DNA sequence with a recombinase, a single-stranded DNA-binding protein (SSB), and a strand-displacing DNA polymerase. In this study, we optimized the reaction conditions of RPA to detect SARS-CoV-2 DNA and RNA using a statistical method to enhance the sensitivity. In vitro synthesized SARS-CoV-2 DNA and RNA were used as targets. After evaluating the concentration of each component, the uvsY, gp32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Labeled amplification can be easily detected by using lateral flow strips ( Jiang et al., 2020a ; Lalremruata et al., 2020 ; Wu et al., 2020 ). The RPA system consists of three main proteins: recombinase, single-stranded DNA binding protein (SSB), and DNA polymerase ( Juma et al., 2021 ). Amplification is initiated by a primer-recombinase complex that invades the DNA double strand on the homologous sequence of the primer.…”
Section: Introductionmentioning
confidence: 99%
“…Labeled amplification can be easily detected by using lateral flow strips ( Jiang et al., 2020a ; Lalremruata et al., 2020 ; Wu et al., 2020 ). The RPA system consists of three main proteins: recombinase, single-stranded DNA binding protein (SSB), and DNA polymerase ( Juma et al., 2021 ). Amplification is initiated by a primer-recombinase complex that invades the DNA double strand on the homologous sequence of the primer.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, we prepared recombinant uvsX, uvsY, and gp32 using an Escherichia coli expression system [ 8 ]. We also examined the effects of each component of the reaction solution on the RPA reaction efficiency and optimized the reaction conditions using a statistical method [ 5 ]. In those studies, uvsX, uvsY, and gp32 were expressed as N- and C-terminal hexahistidine-tagged (His-tagged) proteins with a thrombin recognition site.…”
Section: Introductionmentioning
confidence: 99%
“…When treated with thrombin to cleave the His-tag, uvsY became insoluble while uvsX and gp32 remained soluble [ 8 ]. Therefore, we used untagged uvsX and gp32 and N- and C-terminal tagged uvsY to optimize reaction conditions [ 5 ]. However, it is possible that the uncleaved tag has a negative effect on the RPA reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain PCR-similar molecular testing outside a centralized laboratory, various isothermal (single-temperature) nucleic acid amplification methods have been devised and are in a continuous race to achieve a performance similar to that of PCR tests. The major candidates include recombinase polymerase amplification (RPA) 5 9 , nucleic acid sequence-based amplification (NASBA) or RNA-specific amplification 10 12 , and loop-mediated isothermal amplification (LAMP) 13 . The advantage of isothermal amplification methods over PCR is that they do not require bulky instrumentation, enable rapid (10–60 min) amplification of nucleic acids at a constant temperature (e.g., 37–65 °C) and therefore improve throughput in situations in which large numbers of clinical samples must be processed and facilitate point-of-care diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…As of now, we have not come across any study that has reported the co-assisted amplification of RNA and DNA cycles using an isothermal amplification method. In this study, we aimed to advance the bioengineering of our earlier studies on RNA-specific amplification 11 , 12 and RPA 8 , 9 , 21 and then integrate the essentials of both types of isothermal amplification methods into a simple format of ‘sample-in and answer-out’ with a primary focus on the detection of low copy numbers of viral RNA directly from COVID-19 saliva samples without the need for any laboratory handling or sample preprocessing. In this regard, we report the development of a completely homogeneous, isothermal, highly sensitive, and ultrarapid method for detecting virus RNA target sequences for the on-site (low resource settings) molecular diagnosis of COVID-19 and other infectious diseases.…”
Section: Introductionmentioning
confidence: 99%